Symptom Onset to First-Medical-Contact in ST-Segment Elevation Myocardial Infarction Patients - Balbaa, Amira (My University, 2016)
ST-segment elevation myocardial infarctions (STEMI) make up approximately 25% to 40% of total myocardial infarction (MI) presentations. The total occlusion of the coronary artery that results in a STEMI makes timeliness to reperfusion crucial. Previously, the focus has been on decreasing door-to-balloon time (D2B). Although D2B time plays an important role in achieving timely treatment, it is only one component of the route from symptom onset to reperfusion. It has been shown that total ischemic time is a better predictor of clinical outcomes, including mortality and infarct time. Delays between symptom onset to first-medical-contact (FMC) consume the majority of total ischemic time, and remains one of the main reasons that patients do not receive timely care. Factors affecting symptom onset to FMC for STEMI patients receiving primary PCI as a method of reperfusion at the Aswan Heart Center (AHC) in Egypt and the Hamilton General Hospital (HGH) in Canada were examined using the prospectively collected data held in the STEMI registries at these sites and a modified version of the Response to Systems Questionnaire applied in Egypt. Exploring factors linked to early and late presentation in STEMI patients showed that delays were associated with gender, smoking, cardiac history, cardiogenic shock and mortality rate. Furthermore, the type and number of symptoms, presence and actions of bystanders, emotional response and the actions of the patients, as well as transportation time was shown to be different among delay groups.
Keywords: Time Delays; STEMI